Habsburgs Despotie und die Hochkultur des Asservierens. Zum Aufheben und Liegenlassen österreichischer Bürokratieliteratur: [Habsburg Despotism and the High Culture of “Asservieren”. On Preserving and Shelving Austrian Bureaucratic Literature] (Studia austriaca, 2017)
The Austro-Hungarian bureaucracy is often remembered for its practices of delay (or, to use a term emphasized in The Man without Qualities, for its practices of «Asservieren»). This is the case in the reception of literary texts as sources and as culture, in the marginalization of «new objectivity» texts, in the production of autobiographical texts, and in the aesthetics of contradiction. This article examines the grave consequences for the understanding of domination.